Rozwiązane

Uzasadnij twierdzenie:

a) tg^2alfa(1 - sin^2alfa) = sin^2alfa
b) (sinalfa - cosalfa)^2 = 1 - 2sinalfacosalfa



Odpowiedź :

Odpowiedź:

a)

tg²α(1 - sin²α) = sin²α

1 - sin²α = cos²α

tg²α * cos²α=sin²α

sin²α/cos²α * cos²α= sin²α

sin²α = sin²α  c.n.u

b)

(sinα - cosα)² = 1 - 2sinαcosα

Stosujemy wzór skróconego mnożenia

(a - b)² = a² - 2ab + b² , gdzie a = sinα i b = cosα

sin²α - 2sinαcosα + cos²α = 1 - 2sinαcosα

sin²α + cos²α - 2sinαcosα = 1 - 2sinαcosα

sin²α + cos²α = 1

sin²α + cos²α - 2sinαcosα = 1 - 2sinαcosα

1 - 2sinαcosα = 1 - 2sinαcosα  c.n.u